Potential Clinical Applications of Exosomal Circular RNAs: More than Diagnosis - Molibeli, Kearabetsoe Matseliso; Hu, Rong; Liu, Yuze; Xiong, Dehui; Tang, Lijun (Frontiers in Molecular Biosciences, 2021)
Exosomes are small vesicles derived from cells used as intercellular communication goods in various diseases including tumors, neurodegenerative diseases, cardiovascular diseases and other diseases. Circular RNAs (circRNAs) are a novel family of non-coding endogenous RNAs generated through backsplicing, catalyzed by RNA polymerase Ⅱ. These non-coding RNAs have been proposed to regulate gene expression by acting as miRNA sponges, RNA-binding protein regulation and translational capabilities. Genome-wide RNA-seq analyses discovered that circRNAs were enriched in exosomes compared to parental cells. Little attention has been dedicated to exosomal circRNAs(exo-circRNAs). However, research has demonstrated that exo-circRNAs may have important regulatory functions because of their stability in cells and within exosomes. If well understood, the precise roles and mechanisms of exo-circRNAs may increase the potential clinical applications of these molecules as markers in the diagnosis, prognosis and treatment of various diseases. In this review, we outline recent findings regarding exo-circRNAs which includes their functions and highlights their potential applications and therapeutic targets in human diseases.